2018
DOI: 10.1111/echo.14186
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional echocardiography of mechanical circulatory support devices

Abstract: Two‐dimensional echocardiography is a crucial component for assessing the position and function of mechanical circulatory support devices, but three‐dimensional echocardiography provides additional information to aid in management and may improve accuracy in the assessment of these devices. In this article, we review the utility of three‐dimensional echocardiography of various mechanical circulatory support devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…This study showed that 22 patients (21.57%) experienced cardiovascular events during the 2-year follow-up after PCI, and this finding was consistent with the results of one clinical report [17]. A variety of imaging techniques can be used to evaluate the efficacy and prognosis of patients after surgery, such as coronary angiography; however, this examination exhibits the disadvantages of invasiveness and high cost [18,19]. Therefore, more reasonable and scientific evaluation methods for prognosis must be explored.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that 22 patients (21.57%) experienced cardiovascular events during the 2-year follow-up after PCI, and this finding was consistent with the results of one clinical report [17]. A variety of imaging techniques can be used to evaluate the efficacy and prognosis of patients after surgery, such as coronary angiography; however, this examination exhibits the disadvantages of invasiveness and high cost [18,19]. Therefore, more reasonable and scientific evaluation methods for prognosis must be explored.…”
Section: Discussionsupporting
confidence: 87%